2019
DOI: 10.1136/oemed-2019-105843
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to traffic noise and gestational weight gain and postpartum weight retention: a cohort study

Abstract: ObjectivesTransportation noise has been associated with markers of obesity. We aimed to investigate whether road traffic and railway noise were associated with weight gain during and after pregnancy.MethodsAmong the women participating in the Danish National Birth Cohort, 74 065 reported on weight before and during the pregnancy (gestational week 30) and 52 661 reported on weight before and 18 months after pregnancy. Residential address history from conception to 18 months after pregnancy was obtained in natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…66,67 While evidence is still emerging, the currently available research suggests an association between exposure to road traffic noise and an increased risk of adiposity. Interestingly, this was shown in both child cohorts, 69,70 a pregnancy cohort, 68 and adult and elderly populations, [65][66][67] suggesting that exposure to road traffic noise may affect the risk of adiposity throughout life. It is, thus, likely that adiposity is on the mechanistic pathway between noise and cardiometabolic disease, and epidemiological studies should, therefore, avoid adjustment for body mass index, as this could result in overadjustment and underestimation of actual effects.…”
Section: Diabetes and Obesitymentioning
confidence: 94%
See 1 more Smart Citation
“…66,67 While evidence is still emerging, the currently available research suggests an association between exposure to road traffic noise and an increased risk of adiposity. Interestingly, this was shown in both child cohorts, 69,70 a pregnancy cohort, 68 and adult and elderly populations, [65][66][67] suggesting that exposure to road traffic noise may affect the risk of adiposity throughout life. It is, thus, likely that adiposity is on the mechanistic pathway between noise and cardiometabolic disease, and epidemiological studies should, therefore, avoid adjustment for body mass index, as this could result in overadjustment and underestimation of actual effects.…”
Section: Diabetes and Obesitymentioning
confidence: 94%
“…Few prospective cohort studies have investigated the effects of exposure to transportation noise on the risk of developing adiposity. 65–70 The measures of adiposity varied across the studies, with 4 studies investigating effects on weight gain/body mass index, 65,66,68–70 2 studies on waist circumference changes, 65,66 and 2 studies on the risk of obesity/overweight. 66,67 While evidence is still emerging, the currently available research suggests an association between exposure to road traffic noise and an increased risk of adiposity.…”
Section: Epidemiological Evidencementioning
confidence: 99%
“…In support of noise as a risk factor for type 2 diabetes, four longitudinal cohort studies have indicated that transportation noise increases the risk of developing overweight [ [118] , [119] , [120] , [121] ], which is a major risk factor for diabetes. Although the indicators of obesity investigated displayed some variation across the studies (body mass index (BMI), waist circumference, and weight gain), associations were generally observed between road traffic noise and markers of obesity.…”
Section: Health Impact Of Transportation Noisementioning
confidence: 99%
“…The evidence linking road traffic noise to obesity has significantly expanded since the previous evaluation by the WHO. At that time, only three cross‐sectional studies were available, leading to a conclusion of “very low‐quality evidence.” 28 , 29 , 30 Since then, there has been notable progress in research in this area. 30 Three longitudinal studies investigating the relationship between road traffic noise and measures of obesity in adults have been published.…”
Section: Cardiovascular Risk Factors and Noise Pollutionmentioning
confidence: 99%
“…[28][29][30] Since then, there has been notable progress in research in this area. 30 Three longitudinal studies investigating the relationship between road traffic noise and measures of obesity in adults have been published. These studies have explored various.…”
Section: Obesity and Noise Pollutionmentioning
confidence: 99%